A model for the ethylene-mediated auxin distribution under Cr(VI) stress in Arabidopsis thaliana. (3rd August 2018) - Wakeel, Abdul; Gan, Yibo
ABSTRACT: Chromium is one of the top 20 highly toxic heavy metals, which affect agricultural land and economically important crops all over the world. The plant responds to cope with the adverse effects caused by exogenous stimuli. The most important plant's growth, as well as stress response components, are the diverse group of phytohormones. Plant root being the first organ that counters soil contaminant, can be severely damaged. Auxin and ethylene are the most important phytohormones of the root growth and development. It is also reported that auxin is and ethylene play acts synergistically against various abiotic stresses. In a recently published article in Plant, Cell, and Environment we reported that high Cr(VI) levels-induced ethylene mediates auxin distribution. We further reported that Cr(VI)-induced ethylene-mediated auxin is involved in the primary root growth inhibition. In the current, study we proposed a functional model for the Cr(V)-induced ethylene-mediated root growth inhibition by modulating cell cycle and auxin distribution.